APPLICATION TRAFFIC MANAGEMENT TASK - yadi, Mul; Yulianto, Rinto; syamsah, t.n. (DERECHTSSTAAT, 2015)
ABSTRACT In the exercise of police discretion, the Traffic Unit officers Bogor City Police guided by Article 18 paragraph (2) of Law No. 2 of 2002 on the Indonesian National Police "In the circumstances it is necessary to pay attention to laws and regulations, as well as the Code of Professional Ethics of Indonesian Police". One example of the application of police discretion were conducted by the Traffic Police Unit Bogor City to tackle congestion in the city of Bogor, especially at traffic light Bogor Palace is to regulate traffic density without referring to the traffic light.Â  Identify the problem in research 1) How does the application of police discretion in setting tasks traffic? 2) What positive and negative impacts discretionary actions carried out by the police in traffic control? The purpose of this study are as follows: 1) To determine and analyze on the application of police discretion in setting tasks traffic, and 2) To determine and analyze the impact of the actions undertaken by the police discretion in the regulation of traffic. The research method used in this research is normative juridical approach that is used legis positivist concept which states that the law is identical with the norms made written and enacted by institutions or authorities. In addition this concept also saw law as a normative system that is autonomous, closed and detached from public life. The conclusion from this study is the adoption of police discretion in the task of traffic management needs to recognize the Professional Ethics of Police, as very fundamental and important and substantial influence on both the poor implementation of police discretion in the regulation of traffic. Â Keywords: Discretion Police, Traffic Management